2000
DOI: 10.1677/joe.0.1660389
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adrenomedullin infusion on basal and stimulated aldosterone secretion in conscious sheep with cervical adrenal autotransplants

Abstract: In vivo and in vitro studies have shown conflicting effects of adrenomedullin (ADM) on the secretion of steroid hormones from the adrenal gland. While some investigators report no effect of this peptide on the output of various hormones, others have reported both stimulatory and inhibitory roles for ADM. We have shown that basal aldosterone secretion rate (ASR), in conscious sheep with cervical adrenal autotransplants, did not change when ADM was infused directly into the adrenal arterial supply. While not aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 63 publications
2
4
0
Order By: Relevance
“…The mechanisms underlying this stimulation of renin cannot be determined from our study but might include the lower renal perfusion pressure with ADM compared with control and a direct action of the peptide on the juxtaglomerular apparatus (Jensen et al 1997). Despite the higher levels of PRA with ADM than vehicle control, plasma aldosterone levels remained similar to control levels, consistent with relative inhibition of aldosterone secretion by ADM as observed previously by others (Nussdorfer et al 1997, Petrie et al 2000, Salemi et al 2000.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The mechanisms underlying this stimulation of renin cannot be determined from our study but might include the lower renal perfusion pressure with ADM compared with control and a direct action of the peptide on the juxtaglomerular apparatus (Jensen et al 1997). Despite the higher levels of PRA with ADM than vehicle control, plasma aldosterone levels remained similar to control levels, consistent with relative inhibition of aldosterone secretion by ADM as observed previously by others (Nussdorfer et al 1997, Petrie et al 2000, Salemi et al 2000.…”
Section: Discussionsupporting
confidence: 87%
“…ADM is natriuretic and diuretic in a number of animal models (Ebara et al 1994, Hirata et al 1995. Hormonal actions attributed to ADM include stimulation of renin-angiotensin system (Parkes & May 1995, Charles et al 1997, Rademaker et al 1997) and suppression of aldosterone secretion (Nussdorfer et al 1997, Petrie et al 2000, Salemi et al 2000. ADM may also modulate atrial natriuretic peptide (ANP) levels although conflicting publications report both inhibition (Sato et al 1997) and stimulation (Rademaker et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this premise are observations from in vitro studies that ADM inhibits angiotensin II and potassium-(but not ACTH-) induced secretion of aldosterone (Yamaguchi et al 1994, Nussdorfer et al 1997, Andreis et al 1998. Recent in vivo studies in sheep (Salemi et al 2000) and humans (Petrie et al 2000), along with the results of the present study, support an action of ADM to suppress angiotensin II-induced aldosterone secretion. A further factor in the pregnant sheep was the inhibitory action of ADM on ACTH.…”
Section: Discussionsupporting
confidence: 90%
“…There are conflicting reports regarding in vivo studies of the action of ADM on aldosterone. Some studies reported inhibition of endogenous (25) and ANG II-stimulated plasma aldosterone (24,29) while other studies report little or no effect (4,5). Despite vigorous activation of PRA and ANG II by ADM, rises in plasma aldosterone were marginally attenuated with ADM compared with responses with pressure-matched doses of NP (P 檄 0.056).…”
Section: Discussionmentioning
confidence: 98%